2006
DOI: 10.1039/b606316k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sr content on the crystal structure and electrical properties of the system La2−xSrxNiO4+δ(0 ≤ x ≤ 1)

Abstract: Materials formulated as La(2-x)Sr(x)NiO(4+delta) (0 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
68
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 22 publications
9
68
3
Order By: Relevance
“…Therefore, these oxygen excess materials caught a lot of interest as cathodes for SOFC applications due to their potentially high oxygen transport property. [5][6]10,13 Most efforts on La 2−x Sr x NiO 4+δ (LSNO) have been devoted to understanding structural stability, electrical and thermal behavior of La 2−x Sr x NiO 4+δ compounds with only a few investigations of the transport of conducting species in the system. 2,[7][8][9][10] Moreover, materials in this group exhibit coefficient of thermal expansion (CTE) values in the range of 12.4-13.6×10 -6 K -1 , close to the common SOFC electrolyte materials such as the ceria-based electrolytes (13.2×10 -6 K -1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these oxygen excess materials caught a lot of interest as cathodes for SOFC applications due to their potentially high oxygen transport property. [5][6]10,13 Most efforts on La 2−x Sr x NiO 4+δ (LSNO) have been devoted to understanding structural stability, electrical and thermal behavior of La 2−x Sr x NiO 4+δ compounds with only a few investigations of the transport of conducting species in the system. 2,[7][8][9][10] Moreover, materials in this group exhibit coefficient of thermal expansion (CTE) values in the range of 12.4-13.6×10 -6 K -1 , close to the common SOFC electrolyte materials such as the ceria-based electrolytes (13.2×10 -6 K -1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thermal strain should play a minimal role in the reorientation due to the nearly equal thermal expansion coefficients of the materials; LSNO being approximately 11.5 Â 10 À6 K À1 whereas STO being approximately 11 Â 10 À6 K À1 . 45,46 It should also be noted that from the XRD pattern in Fig. 1 and the pole figures in Figs.…”
Section: B Role Of Nickel Valence In Reorientationmentioning
confidence: 94%
“…The ASR value of PSNCO1703 at 650 C is 0.314 U cm 2 , while the ASR value can be obtained as low as 0.063 U cm 2 at 800 C. It can be seen that the relaxation frequencies are in the same order of magnitude of 1 Hz, and they show an increasing trend with the increase of testing temperature. This indicates that the ionic transfer at the cathode/ electrolyte interface is promoted due to the increase of testing temperature [27]. The impedance spectra recorded for all compositions at 800 C are presented in Fig.…”
Section: Electrochemical Performancementioning
confidence: 98%
“…It has been reported that the ionic conductivity of this kind of material is only approximately the same order of magnitude as the one of 8YSZ, while the values of electronic conductivity are in the magnitude of 10 1 e10 2 S cm À1 [11]. The electronic conductivity of these oxides almost reaches the requirement for the application as cathode materials and the enhancement of electronic conductivity can be achieved by doping strontium on the A site [22,27]. As for substitution on Ni site in Pr 2 NiO 4þd , our previous work has shown that Pr 2 Ni 0.6-Cu 0.4 O 4 is observed with the best cell performance in the Cu substituted Pr 2 NiO 4þd systems [28].…”
Section: Introductionmentioning
confidence: 96%